2017
DOI: 10.1021/acsami.7b07656
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Morphology of Mono- and Bidoped α-MnO2 Catalysts for Remarkable Enhancement in Soot Oxidation

Abstract: In the present work, nanowire morphologies of α-MnO, cobalt monodoped α-MnO, Cu and Co bidoped α-MnO, and Ni and Co bidoped α-MnO samples were prepared by a facile hydrothermal synthesis. The structural, morphological, surface, and redox properties of all the as-prepared samples were investigated by various characterization techniques, namely, scanning electron microscopy (SEM), transmission and high resolution electron microscopy (TEM and HR-TEM), powder X-ray diffraction (XRD), N sorption surface area measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 68 publications
4
104
0
Order By: Relevance
“…3a) in CeO 2-δ @β-MnO 2 were found to be 642.0 and 653.8 eV, respectively. The two peaks with binding energies of 641.9 eV and 643.6 eV in the deconvolution of Mn 2p 3/2 can be attributed to Mn 3+ and Mn 4+ , respectively, which are in good agreement with those reported for MnO 2 , [35][36][37] indicating the oxidation states of Mn species are Mn 3+ and Mn 4+…”
Section: Characterizationsupporting
confidence: 87%
“…3a) in CeO 2-δ @β-MnO 2 were found to be 642.0 and 653.8 eV, respectively. The two peaks with binding energies of 641.9 eV and 643.6 eV in the deconvolution of Mn 2p 3/2 can be attributed to Mn 3+ and Mn 4+ , respectively, which are in good agreement with those reported for MnO 2 , [35][36][37] indicating the oxidation states of Mn species are Mn 3+ and Mn 4+…”
Section: Characterizationsupporting
confidence: 87%
“…Recently, numerous researchers have focused on MnO 2 ‐based composites or the doping of MnO 2 with metals (e.g., Al, Zn, Ce, Co and Fe) to improve their intrinsic conductivity . For example, Cakici et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,n umerous researchers have focused on MnO 2based composites or the doping of MnO 2 with metals (e.g.,A l, Zn, Ce, Co and Fe) to improve their intrinsic conductivity. [23][24][25][26][27][28][29] For example, Cakici et al prepared ac arbon fiberf abric/corallike MnO 2 nanostructure by using ag reen hydrothermal method,w hich displayed ac apacitance of 467 Fg À1 at 1Ag À1 . [30] Zhou and co-workers reported Al-doped a-MnO 2 , which showed enhancede lectrochemical performance owing Defect engineering is an effective way to modulate the intrinsic physicochemical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work reported on the synthesis of iron‐doped Mn 2 O 3 catalysts (Mn 2− x Fe x O 3 : x = 0.05 to 0.2) for the application of low‐temperature soot oxidation and achieved a T 50 (temperature at 50% soot conversion) of 400°C because of the formation of an increased amount of active oxygen species upon doping . Jampaiah et al fabricated mono‐doped and bi‐doped α‐MnO 2 nanowires and reported that strong redox behavior, number of active sites, surface adsorbed oxygen species, and active crystalline planes of Co and Cu Bi‐doped α‐MnO 2 nanowires were responsible for their highest catalytic soot oxidation activity . However, Mn 2 O 3 doped with other active transition metals for the application in soot oxidation has not been studied and reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…23 Jampaiah et al fabricated mono-doped and bi-doped α-MnO 2 nanowires and reported that strong redox behavior, number of active sites, surface adsorbed oxygen species, and active crystalline planes of Co and Cu Bi-doped α-MnO 2 nanowires were responsible for their highest catalytic soot oxidation activity. 24 However, Mn 2 O 3 doped with other active transition metals for the application in soot oxidation has not been studied and reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%